Association between enrollment factors and incident cognitive impairment in Blacks and Whites: Data from the Alzheimer's Disease Center. Issue 12 (7th October 2019) - Gleason, Carey E.; Norton, Derek; Zuelsdorff, Megan; Benton, Susan F.; Wyman, Mary F.; Nystrom, Naomi; Lambrou, Nickolas; Salazar, Hector; Koscik, Rebecca L.; Jonaitis, Erin; Carter, Fabu; Harris, Brieanna; et al.
Abstract: Introduction: We examined the influence of enrollment factors demonstrated to differ by race on incident mild cognitive impairment and dementia using Alzheimer's Disease Center data. Methods: Differences in rates of incident impairment between non‐Latino Whites and Blacks ( n = 12, 242) were examined with age‐at‐progression survival models. Models included race, sex, education, source of recruitment, health factors, and family history of dementia. Results: No significant race differences in progression were observed in cognitively unimpaired participants. In those with mild cognitive impairment at baseline, Whites evidenced greater risk for progression than Blacks. Enrollment factors, for example, referral source, were significantly related to progression. Discussion: The finding that Blacks demonstrated lower rate of progression than Whites is contrary to the extant literature. Nested‐regression analyses suggested that selection‐related factors, differing by race, may account for these findings and influence our ability to accurately estimate risk for progression. It is potentially problematic to make racial comparisons using Alzheimer's Disease Center data sets.